2015
DOI: 10.1002/2015gl063186
|View full text |Cite
|
Sign up to set email alerts
|

The tilt of mean sea level along the east coast of North America

Abstract: The tilt of mean sea level along the North American east coast has been a subject of debate for many decades. Improvements in geoid and ocean circulation models, and GPS positioning of tide gauge benchmarks, provide an opportunity to produce new tilt estimates. Tilts estimated using tide gauge measurements referenced to high‐resolution geoid models (the geodetic approach) and ocean circulation models (the ocean approach) are compared. The geodetic estimates are broadly similar, with tilts downward to the north… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 52 publications
7
47
0
Order By: Relevance
“…There is a large spatial change in CSL of ∼15 cm within the SAB (south of 36°N) when the GS flows close to shore, but little change in the northern half of the domain, in agreement with geoid models (see Fig. 1b in Higginson et al 2015). Note also that the model results show some southward propagation of signals in the SAB (28°N-34°N and days 45-50; Fig.…”
Section: Numerical Model Setupsupporting
confidence: 82%
See 1 more Smart Citation
“…There is a large spatial change in CSL of ∼15 cm within the SAB (south of 36°N) when the GS flows close to shore, but little change in the northern half of the domain, in agreement with geoid models (see Fig. 1b in Higginson et al 2015). Note also that the model results show some southward propagation of signals in the SAB (28°N-34°N and days 45-50; Fig.…”
Section: Numerical Model Setupsupporting
confidence: 82%
“…For many years, this downward tilt in sea level as one moves north along the coast has been a topic of controversy and disagreement between geodesists and oceanographers (Sturges 1974). While the direction of the along-shore tilt (downward northward) in our relatively simple model generally agrees with the results from observations and other models (Higginson et al 2015), there are some differences.…”
Section: Numerical Model Setupsupporting
confidence: 58%
“…Such studies for the UK have confirmed that there is very little real MSL difference from north to south (e.g., see early studies of this topic by Ashkenazi et al 1994), and that the apparent latitudinal variation in MSL, relative to ODN, had been due to the ODN levelling errors (Penna et al 2013). Similar studies in Australia and North America have also resolved their anomalous historical sea level slopes (Featherstone and Filmer 2012;Higginson et al 2015). …”
Section: Spatial Variation Of Uk Mslsupporting
confidence: 60%
“…For them to yield meaningful projections of future coastal sea level change, models must be able to represent processes at the boundaries and capture the coupling between sea level over the deep ocean and the shallow shelf (cf. Higginson et al 2015;Hughes et al 2015;Saba et al 2016). To that end, understanding the reasons for the dispersion in model performance (Fig.…”
Section: Discussionmentioning
confidence: 99%